2003
DOI: 10.4161/cbt.2.5.440
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Adenovirus Infection of Melanoma Cells by Fiber-Modification: Incorporation of RGD Peptide or Ad5/3 Chimerism

Abstract: The incidence of malignant melanoma has been increasing. Unfortunately, advanced melanomas are rarely curable with standard therapy; therefore, new forms of treatment such as gene therapy are needed. The success of gene delivery or oncolysis depends on the nature of the vector. Adenoviral vectors are advantageous for several reasons; however, they are dependent on CAR (coxsackie and adenovirus receptor) which is deficient or heterogeneously expressed on melanoma cells in situ. Correspondingly, transduction of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
69
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 65 publications
(73 citation statements)
references
References 14 publications
3
69
1
Order By: Relevance
“…5,9,11,12,27,28 In fact, F.5/3 provided consistently stronger augmentation of infectivity than the HI loop-modified F.5 knob in all cancer cell lines analyzed in this study. A complete resistance of all the F.5/3 chimerabased vectors to recombinant Ad5 knob blocking, on the one hand, but clear sensitivity to the recombinant Ad3 knob, on the other, as illustrated by Figure 5, demonstrates ablation of CAR-tropism and strongly suggests that the major interaction of the F.5/3 viruses with cancer cells involves the Ad3 receptor.…”
Section: Discussionmentioning
confidence: 56%
See 2 more Smart Citations
“…5,9,11,12,27,28 In fact, F.5/3 provided consistently stronger augmentation of infectivity than the HI loop-modified F.5 knob in all cancer cell lines analyzed in this study. A complete resistance of all the F.5/3 chimerabased vectors to recombinant Ad5 knob blocking, on the one hand, but clear sensitivity to the recombinant Ad3 knob, on the other, as illustrated by Figure 5, demonstrates ablation of CAR-tropism and strongly suggests that the major interaction of the F.5/3 viruses with cancer cells involves the Ad3 receptor.…”
Section: Discussionmentioning
confidence: 56%
“…12,15,[24][25][26] Thus our data indicate that due to some structural features the Ad3 knob is more refractory to genetic incorporation of the RGD-4C peptide than the Ad5 fiber knob domain.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…Earlier studies which utilized these vectors have demonstrated that the employed MOI elicits optimum gene transfer of target cells based on available cellular receptors. 17 We would also note that the MOIs we employed do not differ substantially from recent microarray studies of adenoviral entry biology, as noted above. 19,20 Changes in gene expression were considered to be significant when P-values were less than 0.05.…”
Section: Resultsmentioning
confidence: 93%
“…The rationale for using the human melanoma cell line, M21, was linked to our previous findings which demonstrate effective adenoviral vector-mediated infection of these melanoma cells by tropism-modified vectors, Ad5lucRGD and Ad5/ 3luc1. 17 Herein, we utilize microarray technology to investigate the resultant changes in gene expression after infection of melanoma cells with recombinant adenoviral vectors containing a wild-type capsid, Ad5luc1, or with tropism-modified adenoviral vectors Ad5lucRGD and Ad5/3luc1.…”
mentioning
confidence: 99%